Achieving ultrahigh volumetric performance of graphene composite films by an outer–inner dual space utilizing strategy. Issue 19 (5th May 2020) - Huang, Cong; Tang, Qunli; Feng, Qiushui; Li, Yanhua; Xu, Yali; Zhang, Yan; Hu, Aiping; Zhang, Shiying; Deng, Weina; Chen, Xiaohua
Abstract : An outer–inner dual space utilizing strategy is reported for the fabrication of an ultrahigh volumetric performance polydopamine-coated dopamine/reduced graphene oxide composite film. Abstract : Graphene films often suffer from low gravimetric capacitance at high density due to low space utilization, resulting in undesirable volumetric performance. Herein, an outer–inner dual space utilizing strategy is reported for the fabrication of a high density yet high gravimetric performance polydopamine-coated dopamine/reduced graphene oxide composite film (DA/rGO@PDA). The DA molecule is introduced into the inner area of the graphene film as a redox-active spacer, which endows the electrode with additional pseudocapacitance, favorable ion accessible area, as well as accelerated ion diffusion kinetics. More importantly, the outer surface of the graphene composite film is covered by the polydopamine layer formed during the hydrothermal process, which is demonstrated to be a pseudocapacitance donor. Consequently, the outer surface and inner space of the DA/rGO@PDA film was utilized simultaneously, which is rarely reported in previous research. Benefiting from the ingenious structure design, DA/rGO@PDA delivers a high gravimetric capacitance of 449.3 F g −1 at a high density of 1.72 g cm −3, corresponding to an ultrahigh volumetric performance of 772.8 F cm −3 . Moreover, the symmetric supercapacitor exhibits excellent volumetric energy density (16.4 W h L −1 ) and cycle stability (90% of its initial capacitance after 5000 cycles at 5 A g −1 ) in an aqueous electrolyte. The outer–inner dual space utilizing strategy promotes new opportunities for paper-like monoliths as energy storage electrode materials.